The prediction of errors and the improvement of data obtained in wind-tunnel heat-transfer tests - Wilson, Donald M.; Naval Ordnance Laboratory (White Oak, Md.) (White Oak, Maryland : United States Naval Ordnance Laboratory, 1970)
The measurement of heat-transfer data in a high-speed wind tunnel is considered in detail. The analysis is restricted to tests where transient temperature measurements are made by thermocouples attached to the back face of a thin-walled model. Methods of estimating the error in obtaining a heat-transfer coefficient due to extraneous heat-transfer rates or the choice of a data-reduction method are presented. The error caused by the presence of a thermocouple in a thin wall was found experimentally. Methods of improving heat-transfer data, including the Thomas-Fitzsimmons conduction correction method, are discussed. (Author).
"24 September 1970".
Includes bibliographical references (pages 15-16)
Mode of access: Internet.
Keywords: Heat -- Transmission; Wind tunnels